Analisis Pengukuran Tingkat Kematangan Tata Kelola Sistem Informasi Manajemen Keuangan Daerah (SIMDA Keuangan) Menggunakan Cobit 5 - Sontri; Antoni, Darius (Jurnal Ilmiah Informatika Global, 2023)
The Musi Banyuasin Regency Government has implemented an information system to support its business processes, one of which is the Regional Financial and Asset Management Agency (BPKAD). To carry out its function in managing regional finances and assets, BPKAD mostly utilizes the Regional Management Information System (SIMDA) which has been used for approximately five years, but has never been evaluated. For this reason, it is necessary to evaluate SIMDA information technology governance. In this study, the author uses a qualitative approach using the Process Assessment Model (PAM) consisting of indicators on process performance and process capability COBIT 5: A Business Framework for the Governance and Management of Enterprise IT which is the material research standards to process primary data and secondary data. The result of the research is that there is a staffing requirement evaluation process carried out by the BPKAD secretary by positioning it to the staffing sub-section in the form of ASN Requirements Formulation, Plan, Fulfillment and Proposal Forms. This study also revealed that there is a process in the backup log in the operation of Simda carried out by the ICT management section of the MUBA Regency BPKAD, the EDM04 process, EA01 Monitor, is at level 2, which means that the process already has good governance, such as being properly managed and controlled. and the APO07, BAI09 and DSS01 processes are at level 1, which means that the process has been carried out by the MUBA Regency BPKAD, the IT governance capability level at SIMDA BPKAD MUBA Regency is on average at level 1.